Relação sociedade e proteção ambiental: estudo no entorno da Área de Proteção Ambiental do Campo de Dunas de Paracuru - CE - Portela, Samuel Victor da Silva (2009)
The Environmental Protection Area (APA) of the Field of Dunes is the largest Conservation Unit (UC) of the City of Paracuru. Comprising for 3909.60 hectares the APA has the environmental characteristics of the dunes that make up an ecosystem of ecological balance naturally fragile and in constant state of risk in relation to human intervention, but with a great ecological value and tourism. This area has a fundamental importance for the city, it is situated near the center of the municipal office and is in the process of increasing urbanization, including in areas of permanent preservation (APP) in its interior. With the present study, we tried to analyze the relations existing between the preservation of the APA of the field of Paracuru Dunes, and the use and occupancy of this by the around communities. The guiding elements for the theoretical and empirical analysis of the issue and execution of this research were the Environment, the Public Power and Society. As research techniques were used, the research literature, documentary research, non-participant observation and structured interviews and participatory research. The results enabled the development of a real scenery and this showed that the lack of synergy between the Public Power and community entities have been disclosed as a factor in worsening environmental conditions and quality of life for residents around the Environmental Protection Area of the Field of Dunes of the City of Paracuru-CE. With the diagnosis of field and the aid of a matrix of responsibilities, built in participatory research, we guide the Public Power and the communities around of the APA on the need to discuss the ideal scenery and analyze its viability, aiming at to construct the viable scenery for the area, under the support of the Environmental and Organic Laws of the Municipality.